A Comparative Study of Prothrombinase and Thrombin Inhibitors in a Novel Rabbit Model of Non-Occlusive Deep Vein Thrombosis - Hollenbach, Stan; Sinha, Uma; Lin, Pei-Hua; Needham, Kathy; Frey, Lisa; Hancock, Tom; Wong, Arnold; Wolf, David (Thrombosis and Haemostasis, 1994)
A quantitative and non-occlusive deep vein thrombosis model was developed in rabbits. We used this model to test the antithrombotic activity of the prothrombinase complex inhibitors factor rXai and its chemical analog glutamyl-glycyl-arginyl chloromethyl ketone inactivated human factor Xa (EGR-Xai), along with the thrombin inhibitors D-phenylalanyl-prolyl-arginyl chloromethyl ketone (PPACK) and heparin. Dose dependent effects of the inhibitors during constant infusion were monitored. Measurements included thrombus weights, hemostatic parameters and both cuticle and ear bleeding times. In this model, factor rXai and EGR-Xai had comparable in-vivo efficacy, and showed 80%-93% inhibition at plasma levels of 6.5 nM (rXai) and 8 nM (EGR-Xai). Effects on ex-vivo clotting times varied among the inhibitors. At 80-100% thrombus inhibition, factor rXai and EGR-Xai had no statistically significant effect, while PPACK extended thrombin clotting time (TCT) times 2.3-fold, and heparin prolonged both activated partial thromboplastin time (APTT), prothrombin time (PT) and TCT ex-vivo clotting times 6.9-, 1.2-, and 7-fold respectively. At these dosages, cuticle and ear bleeding times were prolonged for all inhibitors and showed increases of 177%-389% (cuticle) and 45%-129% (ear). Our results demonstrate that direct inhibition of prothrombinase complex assembly is effective in arresting venous thrombosis.